Valuing Circularity: Sustainable Finance with Real Options methodology - Alloub, Mostafa (AUC Knowledge Fountain, 2024)
This thesis presents an enhanced framework for valuing circular investments based on the Value Hill model using real options analysis. We propose a new flexible numerical methodology for valuing circularity using the Least Squares Monte Carlo simulation (LSMC) method of Longstaff and Schwartz (2001). The Value Hill model of circularity represents the course followed by the value of an asset, specifically after primary use. To validate the efficiency of our model, we conduct an empirical study on the smartphone business using the case of Apple. Results of our empirical analysis show that investing in circularity enhances financial value. Our model enables analysts, managers, and sophisticated investors to make more informed decisions when assessing such projects.